Management of community-acquired pneumonia in immunocompetent adults: updated Swedish guidelines 2017. Issue 4 (3rd April 2018) - Athlin, Simon; Lidman, Christer; Lundqvist, Anders; Naucler, Pontus; Nilsson, Anna C.; Spindler, Carl; Strålin, Kristoffer; Hedlund, Jonas
Abstract: Based on expert group work, Swedish recommendations for the management of community-acquired pneumonia in adults are here updated. The management of sepsis-induced hypotension is addressed in detail, including monitoring and parenteral therapy. The importance of respiratory support in cases of acute respiratory failure is emphasized. Treatment with high-flow oxygen and non-invasive ventilation is recommended. The use of statins or steroids in general therapy is not found to be fully supported by evidence. In the management of pleural infection, new data show favourable effects of tissue plasminogen activator and deoxyribonuclease installation. Detailed recommendations for the vaccination of risk groups are afforded.